New application method for cocoa disease control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
A new method for fungicide application has been developed at the Cocoa Research Unit in Trinidad and Tobago for reducing losses from black pod and other fungus diseases in cocoa. Copper fungicide is incorporated in a collar made from water permeable...